Microfinance and Community Empowerment Through Kampung Madani Program PT Permodalan Nasional Madani - Saragih, M. Aulia Putra; Karunia, R. Luki (KnE Social Sciences, 2025)
Poverty remains an economic development issue in Indonesia. One of the government strategies in poverty alleviation is through microfinance, which includes community empowerment program implemented by PT Permodalan Nasional Madani (member of Ultra-micro Holding SOE). This research aims to describe the implementation of Kampung Madani community empowerment program managed by PT Permodalan Nasional Madani. Based on the previous studies, the Kampung Madani program scheme can be considered as a prototype of empowerment program that is proven to be able to increase community income. The background of this research is the poverty condition in Indonesia and the implementation of microfinance and community empowerment program as an effort to increase the income of micro enterprises and improve the quality of life of the community. This study uses descriptive qualitative methods to identify effective community empowerment models that have a significant impact on the community. The sample used is Cibodas Village, West Bandung Regency, West Java Province, which is considered a successful representation of Kampung Madani.